Practical HTML5 Projects - West, Adrian W.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Practical HTML5 Projects is a collection of valuable web techniques that any developer or designer can use. This book is all about saving time. Busy web developers should not have to plow through pages of theory or history only to discover that no practical applications are provided, nor should they have to read a paragraph five times to extract some meaning from it. All of the techniques within this book are explained using fully worked examples that you can immediately apply to your own projects. With each technique the book provides: A practical and useful example (and a screen shot of the end result where applicable). The markup for a fully worked example. A downloadable template to adapt for use in your own websites. With Practical HTML5 Projects, you can dive straight into the book at the required chapter and immediately find answers to your website problems, and find the sample code you can use to get it right. Start creating websites using the practical examples, summaries, and templates. This book includes topics such as rollover navigation menus without scripts, adding audio and video, rounded corners, drop shadows, adding PayPal services, and much more. It also includes sections on troubleshooting and transitioning to HTML5 and CSS3 to help bring your existing content up to date.
Keywords: Computer science; Computer Science; Computer Science, general